Contact with grandparents and young people’s explicit and implicit attitudes toward older adults - Tiansi Liao; Cuo Zhuoga; Xiaochen Chen (BMC Psychology, 2023)
Abstract Background Given the dramatic rise in population aging and widespread negative attitudes toward older people, it is necessary to understand the factors that affect age-related attitudes among young people in order to improve intergenerational solidarity and reduce ageism. The current study examined young people’s contact with their grandparents and attitudes toward older people on both explicit and implicit levels. Method The sample included 146 Chinese college students (M age = 21.50 yrs, SD = 2.23, 101 females). Participants completed a questionnaire concerning contact with their grandparents(contact quantity and contact quality), perceived typicality of their grandparents, intergroup anxiety, inclusion of other in the self, and explicit attitudes toward older people (aged 65 years or older) in general. Participants were also invited to complete a single-category implicit association test (SC-IAT) to assess their implicit attitudes toward older people. Results The findings indicated that both quantity and quality of contact with grandparents predicted better explicit attitudes toward older people, and contact effects were stronger when one’s grandparents were perceived as being typical of older adults. Contact quantity (not quality) was associated with more favorable implicit attitudes only when one’s grandparents were perceived as highly typical older adults. Contact effects on explicit attitudes were mediated by intergroup anxiety and inclusion of other in the self. Conclusion Our findings on the positive effects of contact with grandparents underscore the importance of promoting intergenerational contact within the family as a starting point to reduce prejudice toward older adults in age-segregated modern societies. Current results also provide insights on how to extend the benefits of grandparent-grandchild contact outside the family by promoting the perceived typicality of one’s grandparents.